2017
DOI: 10.1177/1545968317690832
|View full text |Cite
|
Sign up to set email alerts
|

Improving Prospective Memory in Persons With Parkinson Disease: A Randomized Controlled Trial

Abstract: Background Prospective memory is essential for productive and independent living and necessary for compliance with prescribed health behaviors. Parkinson disease (PD) can cause prospective memory deficits that are associated with activity limitations and reduced quality of life. Forming implementation intentions is an encoding strategy that may improve prospective memory in this population. Objective To determine the effect of implementation intentions on prospective memory performance in PD. Methods This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
5
12
1
Order By: Relevance
“…Our data are consistent with the notion that II is a more robust prospective memory strategy than VR and may help to compensate for PD-related deficits in executive control processes that underlie intention formation and retrieval (Foster, McDaniel, et al, 2017; Kliegel et al, 2011). Previously, we found that although both strategies improved laboratory prospective memory performance among people with PD, II produced larger effects for tasks with higher strategic encoding and attentional monitoring demands (nonrepeated and non-focal tasks, respectively) (Foster, McDaniel, et al, 2017). This study expands on our previous work to show that training in II may also benefit everyday prospective memory among people with PD.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our data are consistent with the notion that II is a more robust prospective memory strategy than VR and may help to compensate for PD-related deficits in executive control processes that underlie intention formation and retrieval (Foster, McDaniel, et al, 2017; Kliegel et al, 2011). Previously, we found that although both strategies improved laboratory prospective memory performance among people with PD, II produced larger effects for tasks with higher strategic encoding and attentional monitoring demands (nonrepeated and non-focal tasks, respectively) (Foster, McDaniel, et al, 2017). This study expands on our previous work to show that training in II may also benefit everyday prospective memory among people with PD.…”
Section: Discussionsupporting
confidence: 89%
“…They were randomly assigned to the experimental (implementation intentions [II]) or control (verbal rehearsal [VR]) encoding strategy group and completed laboratory-based strategy training. Training occurred in the context of the computerized Virtual Week prospective memory test by instructions from the examiner and automated messages from the Virtual Week (for full description and screen shots of the specific version used in this study, see Foster, McDaniel, et al, 2017; for overview, see also Rendell & Henry, 2009). The Virtual Week takes the form of a board game, with one circuit of the board representing one day.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Downregulation of hippocampus VDR was reported in AD ( Sutherland et al, 1992 ; Gezen-Ak et al, 2013 ). Instead, VDR has never been analyzed in PD although some patients have memory deficiency as AD patients ( Foster et al, 2017 ). Therefore we sought to study the specific cell type expressing VDR in DG of hippocampus in MPTP-induced PD mouse model.…”
Section: Resultsmentioning
confidence: 99%